A phenomenological study of the lived experience of re-entry adjustment of Fulbright FLTA alumni from North Africa and South Asia - Marquis, George, author; Kuk, Linda, advisor; Berensek, Alexandra, committee member; Jennings, Louise, committee member; Lynham, Susan, committee member (Colorado State University. Libraries, 2018)
Sojourners returning to their home countries after working or studying in the United States may face challenges in the re-entry adjustment process. Traditionally, much research on the experience of re-entry adjustment has been survey-based, with researcher-crafted questions not allowing for in-depth and nuanced perspectives of the sojourners. Drawing on in-depth, qualitative interviews from nine North African and South Asian alumni of a Fulbright's Foreign Language Teaching Assistants (FLTA) program, this study employed interpretative phenomenological analysis to capture descriptions of participants' lived experience of re-entry adjustment. Interpretative analysis of unique individual lives combined the situated perspectives of both the participants and researcher. While the in-depth interviews revealed unique lived experiences, careful analysis also revealed four superordinate phenomenological themes of re-entry adjustment: Confidence and a Sense of Empowerment; Comparisons of the Home and Host Countries, Heightened Critical Sensitivity, and Adopting a Re-entry Style. The themes offer a clearer picture of the challenges of returning to areas of the world that are quite different in terms of culture and development from the United States. Descriptions of lived experience were infused with strong feelings and emotions that sometimes typified a process of grieving over separation and loss. Data revealed that the participants struggled to make sense of their current home environment and questioned whether returning home was the correct decision. However, data also revealed participants' strong sense of obligation to family and desires of participants to build on their experiences in the United States and achieve impact. Participants described their desire to transfer knowledge, skills, and new perspectives to their home countries, but expected some resistance. The findings suggest that alumni would benefit from opportunities to discuss their re-entry adjustment challenges in a more supportive home culture environment.
Keywords: interpretative phenomenological analysis; phenomenology; culture shock; re-entry adjustment; South Asia; North Africa